Preventing social defeat stress-induced behavioural and neurochemical alterations by repeated treatment with a mix of Centella asiatica, Echinacea purpurea and Zingiber officinale standardized extracts - Costa, Alessia; Micheli, Laura; Sordi, Virginia; Ciampi, Clara; Lucci, Jacopo; Passani, Maria Beatrice; Provensi, Gustavo (Frontiers in Pharmacology, 2024)
Prolonged exposure to stress is a risk factor for the onset of several disorders. Modern life is burdened by a pervasive prevalence of stress, which represents a major societal challenge requiring new therapeutic strategies. In this context, botanical drug-based therapies can have a paramount importance. Here we studied the preventive effects of a repeated treatment (p.o. daily, 3 weeks) with a combination of Centella asiatica (200 mg/kg), Echinacea purpurea (20 mg/kg) and Zingiber officinale (150 mg/kg) standardized extracts, on the chronic social defeat stress (CSDS) deleterious outcomes. After 10 days of CSDS exposure, male mice' performances were evaluated in paradigms relevant for social (social interaction test), emotional (tail suspension test), cognitive (novel object recognition) domains as well as for pain perception (cold plate and von Frey tests) and motor skills (rotarod). Mice were then sacrificed, the spinal cords, hippocampi and frontal cortices dissected and processed for RT-PCR analysis. Extracts mix treatment prevented stress-induced social aversion, memory impairment, mechanical and thermal allodynia and reduced behavioural despair independently of stress exposure. The treatment stimulated hippocampal and cortical BDNF and TrkB mRNA levels and counteracted stress-induced alterations in pro-(TNF-α, IL-1β and IL-6) and anti-inflammatory (IL4, IL10) cytokines expression in the same areas. It also modulated expression of pain related genes (GFAP and Slc1a3) in the spinal cord. The treatment with the extracts mix obtained from C. asiatica, E. purpurea and Z. officinale may represent a promising strategy to promote resilience and preventing the deleterious effects induced by extended exposure to psychosocial stress.